1995
DOI: 10.1515/cclm.1995.33.3.121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Exercise of Moderate Intensity on Anthropometric Values and Serum Lipids and Lipoproteins

Abstract: The influence of endurance training on serum lipids and lipoproteins was investigated in 20 sedentary males and 14 sedentary females. The total group was trained 3 to 4 times a week for 9 months. After 24 weeks all subjects ran a 15 km-race and after 36 weeks a half-marathon (21 km) race. Anthropometric values were determined before and after the training programme. Blood samples were drawn before the start of the training programme and, in order to avoid the measurement of acute effects, 5 days before both ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…It is possible to assume that a woman close to menopausal age would not obstruct the improvement of serum lipids through exercise. Moreover, the results obtained showed that the most influential factor was each initial value marking the improvement of TC: HDLC ratio and LPO; there are similar reports by others [6,10,30-32]. Consequently, we arrive at the conclusion that exercise is very useful for women around menopause not only to prevent the value from deteriorating but also to return the levels that have already deteriorated.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It is possible to assume that a woman close to menopausal age would not obstruct the improvement of serum lipids through exercise. Moreover, the results obtained showed that the most influential factor was each initial value marking the improvement of TC: HDLC ratio and LPO; there are similar reports by others [6,10,30-32]. Consequently, we arrive at the conclusion that exercise is very useful for women around menopause not only to prevent the value from deteriorating but also to return the levels that have already deteriorated.…”
Section: Discussionsupporting
confidence: 85%
“…It has been clarified that exercise can bring the serum lipids to an acceptable range [4-8]. However, with respect to the sex difference, the effect of exercise is more difficult to be detected in women compared with men [6,9,10]. Also, Motoyama et al .…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study focus on the important interplay between primary risk factors, like blood pressure and lipid levels with fibrinolysis (54). The changes in the haemostatic, fibrinolytic and lipid status as a result of long-term training programme has been separately discussed before (56)(57)(58)(59). The fall in plasma plasminogen activator inhibitor levels, observed in both men and women and the significant decrease in total cholesterol, LDL cholesterol and triacylglycerols in the group of men after nine months of training are known favourable effects of physical conditioning (26,27,30,33,63).…”
Section: Discussionmentioning
confidence: 96%
“…For example, the low-glycemic-load diet was reported to be beneficial in lowering TG and increasing HDL-C, as well as improving plasma glucose control among diabetic patients [10,11]. In addition, several studies with small sample sizes have indicated that increased levels of physical activity could lower total and low-density lipoprotein cholesterol (LDL-C) and increase HDL-C [12][13][14]. In addition, being physically active has been associated with reduced risk of many chronic diseases, such as cancers, heart disease, diabetes, and osteoporosis [15].…”
Section: Introductionmentioning
confidence: 99%